2006
DOI: 10.1007/s00167-006-0227-2
|View full text |Cite
|
Sign up to set email alerts
|

Tendoscopic management of peroneal tendon disorders

Abstract: Endoscopic procedures at the hind foot have become more and more popular over the last few years. However, endoscopy of the peroneal tendon sheath is still not commonly done. We present our experience of scoping the peroneal tendon sheath to help establish more precise diagnosis of the pathology of the peroneal tendons and its associated structures and to treat it in a less invasive way.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
17
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 22 publications
2
17
0
1
Order By: Relevance
“…Tendoscopy is a useful tool to detect and treat peroneal tendon pathology. 31 , 35 It shows several advantages over conventional open surgery including less pain, shorter hospital stays, better cosmesis, and faster recovery. 31 , 32 , 33 , 35 , 36 Endoscopic superior peroneal retinaculum reconstruction is not technically difficult and can be attempted by averaged foot and ankle arthroscopists.…”
Section: Discussionmentioning
confidence: 99%
“…Tendoscopy is a useful tool to detect and treat peroneal tendon pathology. 31 , 35 It shows several advantages over conventional open surgery including less pain, shorter hospital stays, better cosmesis, and faster recovery. 31 , 32 , 33 , 35 , 36 Endoscopic superior peroneal retinaculum reconstruction is not technically difficult and can be attempted by averaged foot and ankle arthroscopists.…”
Section: Discussionmentioning
confidence: 99%
“…17,18 Vega et al reported complete relief of pain in 62.5% in 24 patients with partial ruptures of the peroneals. 19 However, three of these patients with tears did not experience changes in symptoms after tendoscopic debridement.…”
Section: Resultsmentioning
confidence: 99%
“…11 Endoscopic resection of a low-lying muscle belly has been reported. 6 However, the technical details have not been described. In our experience, the peroneus quartus or lowlying muscle belly may jam into the superior part of the superior peroneal tunnel.…”
Section: Introductionmentioning
confidence: 99%